2016
DOI: 10.1111/bld.12172
|View full text |Cite
|
Sign up to set email alerts
|

Health and social care practitioners’ experiences of assessing mental capacity in a community learning disability team

Abstract: Accessible summary The Mental Capacity Act says when and how to assess someone's ability to make a decision and how best to support them to do this. Eight workers in community learning disability teams were interviewed about their experiences of assessing people's ability to make decisions. The workers said that there were a number of areas that they felt were important and which helped them to do good assessments. They also said there were some things that they found difficult. We suggest some changes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Given the complexity of DMC assessment, and the significant consequences of such assessments, the ambiguities in guidance of how to implement it in practice are critical (Murrell & McCalla, ) and may affect how occupational therapists engage in this area of practice. Research across a range of disciplines have reported that HCPs find DMC assessment complex and challenging (Aldhous et al, ; Jayes et al, ; Ratcliff & Chapman, ), with gaps in knowledge and skills, time pressures and conflicting practices being cited as issues. Similarly, many respondents in our study reported that they find this aspect of practice more difficult than other areas of occupational therapy practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of DMC assessment, and the significant consequences of such assessments, the ambiguities in guidance of how to implement it in practice are critical (Murrell & McCalla, ) and may affect how occupational therapists engage in this area of practice. Research across a range of disciplines have reported that HCPs find DMC assessment complex and challenging (Aldhous et al, ; Jayes et al, ; Ratcliff & Chapman, ), with gaps in knowledge and skills, time pressures and conflicting practices being cited as issues. Similarly, many respondents in our study reported that they find this aspect of practice more difficult than other areas of occupational therapy practice.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents in our study highlighted the need for further training in DMC assessment, and the need for practice guidelines to provide a framework for occupational therapists and other HCPs to guide practice in this area, which is consistent with research findings from other jurisdictions and other HCPs (Aldhous et al, ; Seyfried et al, ). However, Ratcliff and Chapman () caution that training may not lead to high‐quality application of the statutory requirements of DMC assessment. A generic one‐size‐fits‐all approach to DMC assessment was not recommended by the therapists in our study, instead the future development of tools, resources and practice guidelines specific to occupational therapy or to particular client groups, may better facilitate the implementation of DMC assessment into routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown if staff members would consider undertaking breast screening as a “large” decision, which could determine how rigorously the process is followed. Ratcliff and Chapman () highlighted several challenges around the issue of capacity assessment. A lack of time and resources were the main challenges highlighted, as assessments need sufficient planning and good information gathering.…”
Section: Introductionmentioning
confidence: 99%
“…Additional challenges centred on working with staff members and families who have a poor understanding of capacity. Ratcliff and Chapman () acknowledged that specific characteristics of the individual can also pose challenges especially if their capacity is considered to be “borderline” or if the individual is overtly influenced by external factors, including support staff. In such cases, there can be indecision or confusion over who is responsible to make the “decision” for the individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation